Analisis Pengaruh Pertumbuhan Penduduk dan Rasio Ketergantungan Terhadap Kemiskinan di Kabupaten Sarolangun - Rohana Rohana; Junaidi Junaidi; Purwaka Hari Prihanto (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The purpose of this research is to analyze population growth, dependency ratio and poverty in Sarolangun district, to analyze the influence of population growth, dependency ratio to poverty in Sarolangun district. The method of analysis used in this study is qualitative descriptive analysis and quantitative analysis using an analysis tool that is doubled linear regression. The results of this study is based on statistical test calculation is hypothesis test using t statistic partially shows the variable Dependecy Ratio t count of 3.651386> t table 1, 77 has a positive and real effect on poverty in Sarolangun district, while population growth t count 0.589322 < t table 1.77 has a negative effect on poverty in Sarolangun district. Based on the f statistic test 6.835044> F table 3.49 shows that silmultan (together) that all multiple linear regression coefficients or population growth variables, and Dependecy Ratio jointly affect the Poverty in Sarolangun District.